Sistematización: la casa de Bernarda Alba; Adaptación criolla santandereana (2020)
In the subjects of Dance Ensemble Ensemble and Theater Ensemble Ensemble it was possible to account for the competences and the different artistic languages: dance, theater, music and design. Also, the pedagogical and humanistic competences. In the first part we will find the background, the practical theoretical reflection, the creation, the dynamics and processes that were taken into account for the assembly. elements associated with the description of the justification and the methodology why we want to systematize, the aspects, what information is available and what is needed, among others, are observed. We continue with the theoretical framework where we approach the concept of general didactics and the didactics of creation, the systematization of an experience and the creation process we will also find a detailed description of the logs. We will find the historical and social context, how the characters were distributed and how it was approached for the creation of the work, its choreography and the music. Finally, we will see how the makeup of each character was made, their costumes, lighting and conclusions.